Managing Risks for a Safer Built Environment in Kenya : Building Regulatory Capacity Assessment - World Bank Group (World Bank, Washington, DC, 2019)
Kenya is an emerging middle income country with a growing share of its population living in urban areas. The country is at a relatively early stage of urbanisation, with around 27 percent of Kenyans living in urban areas, yet projections suggest that by 2050, about half the population will be living in cities. The Nairobi Metropolitan Region in particular will see rapid growth. Nairobi is expected to become a city of more than 6 million people by 2030, up from its currently estimated 4 million. This urbanisation has the potential to improve economic opportunities and living conditions for all Kenyans. However, there are also several challenges associated with this shift and concentration of population. With urbanisation comes a substantial amount of new construction, much of which has occurred in cities with limited capacity to ensure the structures in which people live, work and gather are safely sited and built to withstand both chronic stresses (i.e. fire and spontaneous collapse) and disaster shocks (i.e. earthquakes and floods). Informality, low density development and urban sprawl are common characteristics across Kenya's urban areas. Approximately 61 percent of Kenya's urban population are living in informal settlements. Kenya is exposed to a wide range of hazards, particularly droughts and floods, but also landslides, earthquakes, volcanic eruptions and wildfires. Kenya is also highly vulnerable to recurrent and chronic risks. Its major cities witnessed 26 reported cases of major building collapse since 1996. Furthermore, Kenya is ranked as the 27th most prone country to fire-related deaths in the world. The city of Nairobi recorded 244 fires in 2017 in its informal settlements, claiming the lives of 32 people. In many ways, Kenya is at a crossroads in its efforts of urbanising and developing towards middle income status. Regulatory decisions made now will have a significant impact on the long-term safety, productivity and resilience of the urban built environment.